2021
DOI: 10.3389/fonc.2021.761393
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Radiotherapy in Head and Neck Cancer Elderly Patients: A Feasibility and Safety Systematic Review for the Clinician

Abstract: ObjectiveRadiotherapy (RT) in the head and neck (H&N) site are undoubtedly the most challenging treatments for patients. Older and frail patients are not always able to tolerate it, and there are still no clear guidelines on the type of treatments to be preferred for them. The recommendations for Risk-Adapted H&N Cancer Radiation Therapy during the coronavirus disease 2019 (COVID-19) pandemic provided by the ASTRO-ESTRO consensus statement achieved a strong agreement about hypofractionated RT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Laursen et al investigated 56Gy in 14 fractions (EQD2 of 65Gy) in an elderly patient cohort with a median of 74 years with good tumor response and acceptable tolerability contrasting with the 'Quad shot' regimen (one to three cycles of 14Gy in four fractions given twice daily for two consecutive days) offering effective palliation with minimal toxicity (46,47). A recent review summarized common hypofractionation regimens for elderly patients and concluded that the choice of the correct regimen remains a highly individual decision (48).…”
Section: Discussionmentioning
confidence: 99%
“…Laursen et al investigated 56Gy in 14 fractions (EQD2 of 65Gy) in an elderly patient cohort with a median of 74 years with good tumor response and acceptable tolerability contrasting with the 'Quad shot' regimen (one to three cycles of 14Gy in four fractions given twice daily for two consecutive days) offering effective palliation with minimal toxicity (46,47). A recent review summarized common hypofractionation regimens for elderly patients and concluded that the choice of the correct regimen remains a highly individual decision (48).…”
Section: Discussionmentioning
confidence: 99%
“…Contour delineation is still among the few procedures of the RT workflow with prevalent manual management, which can result in a high risk in inter-observer variability, and above all, it represents one of the phases with the highest time-consuming rate of all the RT workflows [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This feature is extremely relevant in the treatment of head and neck districts, where the location of the main disease and the proximity to organs at risk (OARs) with the associated risk of toxicity make the radiation treatment of H&N cancer patients most complex and time-consuming for a radiation oncology team. In H&N cancers, OAR delineation follows strict guidelines, as various studies have demonstrated that OAR and target volume contouring may be affected by significant inter-observer variability [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature has reported that hypofractionated radiotherapy is safe and effective for older head and neck cancer patients, either with a palliative or curative intent [ 91 ]. Preliminary data of concurrent chemotherapy and hypofractionated IMRT for locally advanced head and neck cancer have shown excellent local control with an acceptable level of toxicity [ 92 , 93 ].…”
Section: Intensity-modulated Image-guided Radiotherapy For Older Canc...mentioning
confidence: 99%